CD4(+)CCR6(+) T cells, but not γδ T cells, are important for the IL‐23R‐dependent progression of antigen‐induced inflammatory arthritis in mice - Razawy, Wida (Eur J Immunol, 2019)
IL‐23 plays an important role in the development of arthritis and the IL‐23 receptor (IL‐23R) is expressed on different types of T cells. However, it is not fully clear which IL‐23R(+) T cells are critical in driving T cell‐mediated synovitis. We demonstrate, using knock‐in IL‐23R‐GFP reporter (IL‐23R(GFP/+)) mice, that CD4(+)CCR6(+) T cells and γδ T cells, but not CD8(+) T cells, express the IL‐23R(GFP). During early arthritis, IL‐23R(GFP)(+)CD4(+)CCR6(+) T cells, but not IL‐23R(GFP)(+) γδ T cells, were present in the inflamed joints. IL‐23R(GFP/+) mice were bred as homozygotes to obtain IL‐23R(GFP/GFP) (IL‐23R deficient/IL‐23R(−/−)) mice, which express GFP under the IL‐23R promotor. Arthritis progression and joint damage were significantly milder in IL‐23R(−/−) mice, which revealed less IL‐17A(+) cells in their lymphoid tissues. Surprisingly, IL‐23R(−/−) mice had increased numbers of IL‐23R(GFP)(+)CD4(+)CCR6(+) and CCR7(+)CD4(+)CCR6(+) T cells in their spleen compared to WT, and IL‐23 suppressed CCR7 expression in vitro. However, IL‐23R(GFP)(+)CD4(+)CCR6(+) T cells were present in the synovium of IL‐23R(−/−) mice at day 4. Finally, adoptive transfer experiments revealed that CD4(+)CCR6(+) T cells and not γδ T cells drive arthritis progression. These data suggest that IL‐23R‐dependent T cell‐mediated synovitis is dependent on CD4(+)CCR6(+) T cells and not on γδ T cells.